Pengaruh Nilai Produksi, Investasi, dan PDRB Terhadap Penyerapan Tenaga Kerja Pada Industri Kecil di Kota Jambi - Junaidi Junaidi; Adi Bhakti; Muhammad Azka Vernanda (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This research aims to find out and analyse the development value of GDRP, investment, production and absorption of labor in the city of Jambi as well as the influence of the value of production, investment and GDRP against labor absorption in the small city of industry Jambi. This type of research is explanatory research (research description). Where as to do hypothesis testing using linear regression equation itself multiple. The results of this study showed a good influence simultaneously or partially between production, investment and GDP against labor absorption in the small industry in the city of Jambi. Where the value of R2 which is 0.946 acquired for. That has meaning to the magnitude of the role or contribution of the variable the value of production, investment and GDRP was able to explain labor absorption in the small industry in the city of Jambi amounted to 94.6%. While the rest of 5.4% is affected by other factors that are not revealed in this study. This research suggests to maintain the condition of the economy that is stable then the Government must encourage sector agriculture and small business medium to keep growing because this sector is resistant to fluctuation and absorb the manpower in the amount large.